Assessing the Economic Value of The Hydropower Energy: The Role of Social Capital and Socio-economic Factors - Ferico Firdauzi, Jovanka; Saptutyningsih, Endah; Boedirochminarni, Arfida (Journal of Economics Research and Social Sciences, 2024)
A good strategy for dealing with environmental problems and improving environmental sustainability. This study examines the extent to which local communities in Yogyakarta, Kulon Progo area, Indonesia are willing to increase hydropower energy. The influence of social capital on people's willingness to get involved was studied using a logistic regression model. Based on the findings, 95% of residents are likely to make financial contributions to improve hydropower energy facilities. Increased social capital, consisting of strong interpersonal relationships, community involvement, and trust, is strongly associated with this engagement. This study adds to the literature by emphasizing the possible function of social capital in the process of adjustment to changes in renewable energy from hydropower energy in households.